1980
DOI: 10.1111/j.1365-246x.1980.tb02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Q determinations in southern Africa using Lg wave amplitudes

Abstract: The amplitude of vertical, short period (1 s) Lg-waves from 575 shallow earthquakes recorded within the distance range 0"-30" by the Rhodesian seismograph network during the period 1968-77 are analysed to separate the effects of earthquake size, epicentral distance and station structure.When corrected for geometrical spreading and Airy phase dispersion the decay of amplitude with distance yields an estimate of anelastic attenuation of 0.160 deg-' which gives an average value of Q (the specific quality factor) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Furthermore, we considered different propagation paths over Zimbabwe as the seismic waves travelled to BUL and found a low Q value of 350 for the Deka fault zone. The Q value of 650 obtained in this study agrees well within error with that of 603 reported by Chow et al (1980) using the multistation, multi-event method, and lies within the range of Q values (454-759) reported by Xie & Mitchell (1990) using a 'back-project' method to image large-scale lateral variations of Lg coda Q. The results obtained are important as the Q value constitutes part of the input data in seismic hazard calculations.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, we considered different propagation paths over Zimbabwe as the seismic waves travelled to BUL and found a low Q value of 350 for the Deka fault zone. The Q value of 650 obtained in this study agrees well within error with that of 603 reported by Chow et al (1980) using the multistation, multi-event method, and lies within the range of Q values (454-759) reported by Xie & Mitchell (1990) using a 'back-project' method to image large-scale lateral variations of Lg coda Q. The results obtained are important as the Q value constitutes part of the input data in seismic hazard calculations.…”
supporting
confidence: 90%
“…where A is the amplitude of the maximum Lg-wave trace, Tis the phase period at the point of maximum amplitude and B(A) is an empirically determined term that is a function of angular distance, A. Details on the determination of B ( A ) and mb (BUL) are given by Henderson (1974) andChow et al (1980). For events occurring within the chosen radius, the most prominent seismic phase on the seismogram is the Lg-wave complex.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earthquake magnitudes in this catalogue are homogenized to BUL magnitudes. BUL reports magnitudes of m,(Lg) type that are on average 0.16 units higher than ISC mh values (Chow et al 1980). Considering the 0.16 magnitude bias as lying within acceptable magnitude error limits, the BUL m,(Lg) magnitudes may be accepted as comparable to ISC reported values.…”
Section: Datamentioning
confidence: 73%